Are all edges equal? Microclimatic conditions, geographical orientation and biological implications in a fragmented forest - Bernaschini, María Laura; Trumper, Eduardo Victor; Valladares, Graciela; Salvo, Adriana (Elsevier, 2024)
In fragmented forests the edges experience changes in microclimatic conditions, which are referred to as “abiotic edge effect”, and differ according to geographical orientation and season. These microclimatic changes could influence the development rate of the organisms (particularly for movement- restricted ones like leaf miner larvae and their parasitoids) and, consequently, their population dynamics. The aim of this study was to compare the abiotic edge effect in differently oriented edges in summer and winter seasons, and evaluate possible implications on insect development, using a simulation based on a degree-day approach. To compare the abiotic edge effect, we took continuous and point measurements of microclimatic variables such as temperature, humidity, wind velocity and interception of photosynthetically active radiation in three microhabitats: interior (I), north-facing edges (NE) and south-facing edges (SE) of six fragments of Chaco Serrano forest, in winter and summer seasons. As we expected, the microclimatic edge effect was greater in NE compared to SE in both seasons. In winter, the differences were more pronounced only for continuous measurements of temperature. Our simulation exercise suggested that differences in temperature among microhabitats may have biological implications on insect populations, affecting their development time. At larger scales, an increase of temperature could lead to more frequent pest outbreaks which could extend their distribution range to higher latitudes. Our f indings emphasize the need to consider geographical orientation and season variations when studying edge effects on insect populations. In the context of climate change, organisms could restrict their distributions to habitats with more suitable conditions, becoming microrefuges that could allow them to survive. Moreover, in fragmented landscapes, identifying microhabitats benefitting or harming insect populations is an important step to design management strategies towards pest control or natural enemy conservation in agricultural settings.